Expression of the gap junction protein connexin36 in small intensely fluorescent (SIF) cells in cardiac parasympathetic ganglia of rodents. (10th January 2023) - Singhal, P.; Senecal, J.M.M.; Nagy, J.I.
Highlights: SIF cells in cardiac parasympathetic ganglia of adult mice and rats express Cx36. Connexin36 was detected in SIF cells early during development. Enhanced green fluorescent protein reporter for Cx36 expression was detected in SIF cells. Immunofluorescent Cx36-puncta appeared at appositions between SIF cells. SIF cells may express Cx36-containing gap junctions to coordinate hormonal secretion. Abstract: In mammals, several endocrine cell types are electrically coupled by connexin36 (Cx36)-containing gap junctions, which mediate intercellular communication and allow regulated and synchronized cellular activity through exchange of ions and small metabolites via formation of intercellular channels that link plasma membranes of apposing cells. One cell type thought to be endocrine-like in nature are small intensely fluorescent (SIF) cells that store catecholamines in their dense-core vesicles and reside in autonomic ganglia. Here, using immunofluorescence approaches, we examined whether SIF cells located specifically in cardiac parasympathetic ganglia of adult and neonatal mice and adult rats follow patterns of Cx36 expression seen in other endocrine cells. In these ganglia, SIF cells were identified by their distinct small soma size, autofluorescence at 475 nm, and immunolabelling for their markers tyrosine hydroxylase and vesicular monoamine transporter-1. SIF cells were often found in pairs or clusters among principal cholinergic neurons. Immunofluorescence labelling of Cx36 occurred exclusively as fine puncta that appeared at contacts between SIF cell processes and somata or at somato-somatic appositions of SIF cells. These puncta were absent in cardiac parasympathetic ganglia of Cx36 null mice. Transgenic mice expressing enhanced green fluorescent protein reporter for Cx36 expression displayed labelling for the reporter in SIF cells. The results suggest that Cx36-containing gap junctions electrically couple SIF cells, which is consistent with previous suggestions that these may be classified as endocrine-type cells that secrete catecholamines into the bloodstream in a regulated manner.